Rehydration effect of qingshu buye decoction on exercise and high temperature-induced dehydration - Huanyu Jiang; Jiankun Gao; Huan Wang; Lin Zhao; Yingduo Yang; Jiahua Ma; Shan Gu; Fenglin Hu; Quanyu Du; Fei Wang (Journal of the International Society of Sports Nutrition)
Objective The aim of this study was to conduct a comprehensive evaluation of the rehydration efficacy of QSBYD and elucidate its potential underlying mechanism.Design 38 participants were randomly assigned to receive either QSBYD or placebo before and after exercise and heat-induced dehydration. Hydration indicators were measured over time. Blood tests assessed cellular anaerobic respiration metabolites, serum inflammatory markers, and coagulation markers. Perceptual measures of thirst, fatigue, and muscular soreness were also taken.Results QSBYD consumption resulted in lower urine volume (Control vs. QSBYD: 260.83 ± 167.99 ml vs. 187.78 ± 141.34 ml) and smaller decrease in percentage of nude body weight change from baseline (Control vs. QSBYD: −0.52 ± 0.89% vs. −0.07 ± 0.52%). Although no significant differences in urine specific gravity, QSBYD resulted in reduced urine volume at 120 min, suggesting improved fluid retention. Furthermore, QSBYD resulted in lower levels of IL-1β (Control vs. QSBYD: 2.40 ± 0.68 vs. 1.33 ± 0.66 pg/mL), suggesting QSBYD may provide benefits beyond hydration.Conclusion Further investigation into the underlying mechanisms and long-term effects of QSBYD on hydration is warranted. QSBYD may be an effective alternative to commercial sports drinks in mitigating dehydration effects.